Fuel Truck Sdn. Bhd. / Nur Fahira Abdul Halim ... [et al.] - Abdul Halim, Nur Fahira; Suduki@Yahaya, Nor Fatin Nabilah; Kamarudin, Nurhafizah; Abdul Razak, Nur Liyana Syamimi; Ramli, Nurulhuda Ainaa (2021)
This report is related to student projects in doing business related to Business Model Canva. The purpose of this project should be comply with the studies related to the Principle of Entreprenuership (ENT530). Student need to create a business group project and and this business needs to be done like the real situation. Every business planning and product create by us will follow the things that have been set by the study related to Business Model Canva. Based on this project, we have established a company called Fuel Truck which is a refueling service for vehicles. Our target is for every vehicle user who has trouble refueling. So we will do the service by coming to their location to help them solve the problem. We ensure that each of our services will be performed to the best of our ability and ensure safety for all road users. Our fuel product is also not an arbitrary result, it is the result of our company's collaboration with a well - known company, Petron Miles.